ANALISIS WACANA KRITIS PEMBERITAAN KASUS PENYALAHGUNAKAN NARKOTIKA OLEH ANGGOTA POLISI KOMPOL YUNI DI DETIK.COM - Zikri Fachrul Nurhadi; Heri Hendrawan; Agi Sugiana (Prodi Ilmu Komunikasi Universitas Putera Batam, 2022)
This research was motivated by the emergence of news about the abuse of narcotics by unscrupulous members of the police, Kompol Yuni, which had become the talk of the wider community, so that many media reported on this case, including detik.com. The purpose of this study was to explain the level of text, social cognition, and the social context of the law of imprisonment by the police officers at detik.com. The research method in this study uses descriptive qualitative with a critical paradigm. The theory used is the theory of critical discourse analysis of the Teun A Van Dijk model. While the data collection techniques used are interviews, literature study, and documentation. With journalists, members of the police, and also members of the National Narcotics Agency. The results showed that at the text level, the elements of the macro structure, superstructure, and micro structure explained an unfavorable situation experienced by the Greek composer. At the level of social cognition, journalists tend to see that Kompol Yuni is in the wrong and this case is interesting news that can be consumed by the public. The level of social context in this news discourse is the practice of power carried out by detik.com against published news and the existence of full access power in handling cases by the West Java Regional Police Propam. From the results of the study, it can be said that reporting on Narcotics by the yuni police at the level of text, social cognition, and social context both highlighted the yuni police as the main role in this case.